2010
DOI: 10.1002/ejic.201000692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Studies of Organotin(IV) and Organolead(IV) Thiophene‐2‐thiocarboxylate

Abstract: A few organotin(IV) ([R2SnCl2], [R3SnCl]; R = Me, Ph, nPr, or nBu) and organolead(IV) ([Ph2PbCl2], [Ph3PbCl]) compounds that contain the thiophene‐2‐thiocarboxylate ligand have been synthesized and characterized by 1H, 13C, 119Sn NMR; FTIR; and UV/Vis spectroscopy. The molecular structures of some of the compounds were studied by single‐crystal X‐ray diffraction. Structures and electronic transitions have been explained on the basis of DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The C-HÁ Á ÁO/S distances and angles ( Table 2) are quite comparable to those reported earlier [18,36,37]. CHÁ Á ÁS interactions of two molecules are such that they form a couple of molecule facing each other.…”
Section: Crystal and Molecular Structuressupporting
confidence: 79%
See 1 more Smart Citation
“…The C-HÁ Á ÁO/S distances and angles ( Table 2) are quite comparable to those reported earlier [18,36,37]. CHÁ Á ÁS interactions of two molecules are such that they form a couple of molecule facing each other.…”
Section: Crystal and Molecular Structuressupporting
confidence: 79%
“…Continuing our studies on thiocarboxylate complexes [16][17][18] we here report the synthesis and characterization of the pdtc complexes of Cp 2 Ti(IV) and Cp 2 Zr(IV). The significance of the present study may be viewed not only in terms of the ligand's ability to stabilize uncommon oxidation state (Ni 3+ ) and unusual structural motifs [19] (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…In none of the cases the sulfur atom of the thiophene ring is involved in bonding with the metal. Very recent studies from our laboratory have showed that the thiophene sulfur carries a partial positive charge in the case of thiophene-2-thiocarboxylates and a dative bond from this sulfur is not quite favourable [38]. The triphenyltin and triphenyllead dithiocarbamates can be used as single source precursors for the preparation of the corresponding metal sulfides.…”
Section: Resultsmentioning
confidence: 98%
“…Thiophene-2-thiocarboxylic acid was prepared by reported procedure [22]. Sodium salt of thiophene-2-thiocarboxylic acid was obtained by reacting the acid with sodium methoxide in stoichiometric ratio.…”
Section: Reagents and General Proceduresmentioning
confidence: 99%
“…We have chosen thiophene-2-thiocarboxylate because of the fact that it contains an additional sulfur atom which could affect the structure and bonding of the complexes [22].…”
Section: Introductionmentioning
confidence: 99%